IDENTIFIKASI JENIS DAN KARAKTERISTIK POHON PENGHASIL BUAH-BUAHAN DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Ika Purnama; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The Forest Reserve of Kenegerian Rumbio has potential as producing trees of forest fruit. Research on the identification of the type and characteristics of the fruit-producing trees in surrounding the Forest Reserve of Kenegerian Rumbio has not been done, so the data and clearer information of the fruit-producing trees has not been available. This study aims to determine the type and characteristics of the fruit-producing trees in Panoghan zone and Sialang Layang zone of the Forest Reserve of Kenegerian Rumbio. This research was conducted by using the method of track / transect with a width of 20 meters and a length of 500 meters. The transect position in the field was determined by using Purposive Sampling technique. Based on observations from both transects, 15 species of fruit-producing trees with the number of individuals 58 fruit-producing trees were found , which each transect has different individual number. Results of tree species diversity index of fruit-producing trees in Panoghan zone is 1.96 and Sialang Layang Zone is 2.3, which means included in the medium category.Keywords: Identification of Species,Fruit- Producing Trees, Species Diversity Index, Forest Reserve of Kenegerian Rumbio